Gambaran tingkat pengetahuan kepala keluarga tentang rumah sehat di kampung Cibogo desa Rancabango Kecamatan Tarogong Garut - Iis Yulianti; Iwan Shalahuddin; Nina Sumarni (Holistik Jurnal Kesehatan, 2021)
Knowledge of a healthy house among householders at Cibogo village Rancabango Tarogong –Garut Background: The house is a residence that functions as a place to nurture the family. A healthy house is a house that can meet healthy criteria, including meeting the physiological and psychological needs of its inhabitants, meeting the prevention of disease transmission and meeting the prevention of accidents. The impact of an unhealthy home is causing and transmitting various types of diseases, especially environmental-based diseases.Purpose: To determine of the Knowledge of a healthy house among householders at Cibogo village Rancabango Tarogong -GarutMethod: A quantitative descriptive with total sampling techniq. The locations at Cibogo village Rancabango Tarogong –Garut with respondents as 159 of householders.Results: Finding that the level of knowledge of 159 householders about healthy homes of 40.9% have a poor knowledge, of 36.5% have enough knowledge and of 22.6% have an excellent knowledge.Conclusion: The level of knowledge of householders about a healthy house mostly was in a category of lacking, and they need further information by competent resources regarding a healthy house.Keywords: Knowledge; Healthy House; HouseholdersPendahuluan: Rumah adalah suatu hunian yang fungsinya sebagai tempat untuk membina keluarga. Rumah yang sehat yaitu rumah yang dapat memenuhi kriteria sehat diantaranya memenuhi kebutuhan fisiologis dan psikologis penghuninya, memenuhi pencegahan penularan penyakit serta memenuhi pencegahan terjadinya kecelakaan. Dampak yang ditimbulkan dari rumah yang tidak sehat dapat menyebabkan dan menularkan berbagai jenis penyakit, terutama penyakit berbasis lingkungan.Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran tingkat pengetahuan kepala keluarga di Kampung Cibogo Desa Rancabango Kecamatan Tarogong Garut. Metode: Deskriptif kuantitatif dengan teknik total sampling. Lokasi di Desa Cibogo Rancabango Tarogong – Garut dengan responden 159 kepala keluarga.Hasil: Tingkat pengetahuan kepala keluarga tentang rumah sehat yaitu 40.9% memiliki pengetahuan buruk, 36.5% memiliki pengetahuan yang cukup dan 22.6% memiliki pengetahuan yang baik.Simpulan: Tingkat pengetahuan kepala rumah tangga tentang rumah sehat sebagian besar berada pada kategori buruk, dan mereka membutuhkan informasi lebih lanjut dari sumber daya yang kompeten tentang rumah sehat.